Strategic planning with a focus on non-profit companies: Fonulibre case - Bejarano Parra, Gustavo Andrés; Luna Castellanos, Miguel Yamid (Ingeniería Solidaria, 2021)
Introduction: This article is the product of the research “Development of a strategic planning system in the employee fund of the Universidad Libre “ carried out during 2019 and 2020. Problem: There is a lack of characterization, distribution of responsibilities, definition of goals, strategies and objectives, definition of times and indicators of compliance of the board of directors. Objective: The research aims to develop a strategic planning system to ensure the management and control of the fund. Methodology: A diagnosis was made with the information collected from the observation and interviews con-ducted with members of the board and the manager to be analyzed and develop the strategic plan based on the methodology of the Balanced Scorecard (BSC). Results: Lack of organization is linked to the lack of characterization, distribution of responsibilities, definition of goals, strategies, objectives, and compliance indicators of the board of directors generates non-compliance with the duties acquired. Conclusion: This project seeks to create a new structure on the board of directors that allows to create order in the responsibilities acquired and control the advancement and fulfillment of those responsibilities. Originality: A new structure is proposed in the employee fund of the Universidad Libre. Limitations: Despite the approval of the new structure by the members of the board of directors, the model has not yet been validated.